PEDAGOGICAL COMPETITION AS A PROFESSIONAL MEANS C AMOREALIZATION OF STUDENTS IN EXTRACURRICULAR ACTIVITIES HIGHER PEDAGOGICAL EDUCATIONAL INSTITUTION (Pedagogy of Higher and Secondary Education, 2022)
We study the organization of pedagogical competition for professional self-realization of future teachers in class work higher pedagogical educational institution.
Keywords: students; pedagogical competition; professional self-realization; field work; higher teacher education institution